Collage of confusion: An analysis of one university's multiple plagiarism policies. (February 2021) - Merkel, Warren
Abstract: Plagiarism is a major concern for institutions of higher education, whose stance on the controversy is often reflected in the form of plagiarism policy. Previous studies have examined these policies as individual documents or in relation to other institutions' policies. Yet little attention has been paid to the multiple plagiarism policies of one institution. The purpose of this study was to examine the plagiarism policies of nine Colleges at the University of Iowa, a public US university whose students often take foundational, cross-disciplinary courses as part of their degree requirements and therefore potentially negotiate multiple policies. Critical Discourse Analysis (Fairclough, 1992) was adopted to examine the differing discourses of the policies. Findings reveal that discourses of authority and ethics are prevalent in all the policies, and that comprehending how the policies correlate to their individual disciplines may prove problematic for students.